Synchronization of Compass Module with Pressure and Temperature Sensor System for Autonomous Underwater Vehicle (AUV) - Harun, Mohamad Haniff; Mohd Aras, Mohd Shahrieel; Md Basar, Mohd Farriz; Abdullah, Shahrum Shah; Mohd Annuar, Khalil Azha (Universiti Teknologi Malaysia, 2015)
This paper describes the synchronization of compass module with pressure and temperature sensor system for an Autonomous Underwater Vehicle (AUV). In general this project is the result of a combination of existing technology for underwater sensory to produce a complete system that aims to identify the position of the AUVs based on AUV degree of freedom. This can be done with the help of compass module that can find and order the AUV is moving at a fixed angle. This created a system that aims to obtain data on pressure and temperature in the AUV. Not only that, the project also aims to prove that the relationship between pressure and depth of the water and the relationship between pressure and temperature. All data gathered is capable of helping in the preparation of an AUV that can accommodate high pressure according to the depth to destination.